Postmodernism versus state during pandemic period. The case of Poland - Jakimowicz-Pisarska, Iwona (HAPSc Policy Briefs Series, 2020)
The last few months because of COVID-19 pandemic we were able to observe the new challenge for nation states, state’s structures and their leaders. Moreover, in the whole world, governments still have to reorganise the states’ functioning and adapt new tools and solutions to unknown conditions. As usually, unpredictable issues push the states to modernisation and enquire searching more and more convenient transformation of the state’s structure. What is more, this dynamic challenge, which creates an unavoidable situation, betray the weakest and the strongest faces of each state in the world. This text is focused on the European experiences and pays the readers’ attention on the examples of European state’s reactions in the face of pandemics. The aim of the author is to show the issues which appeared visibly and undoubtedly in European states’ functioning on the example of particular decisions and actions taken the last few weeks.